Education as Human Knowledge in the Anthropocene - Wulf, Christoph, 1944-
1 online resource (248 pages).
Keywords: This book examines the concepts of the Anthropocene and globalisation in our society and the changes that these are bringing about in education and human learning. The book argues that there needs to be reflexive approach to issues that affect the fate of the planet and the future of humans, brought about by an education that looks to the future. Wulf argues that a change in education and socialization can only succeed based on an understanding of previous educational ideas, and considers the significance of Confucianism and spiritual education that emerged in the East. The book traces key educational ideas throughout history to show how education and human knowledge are closely linked, highlighting the need for us to pay careful attention to repetition, mimesis and the imagination in learning. It shows how a future-oriented education must engage with issues of peace and violence, global citizenship and sustainable development. This timely and compelling book will be of great interest to researchers, academics and students in the fields of philosophy of education, the history and anthropology of education, sustainability education and global citizenship education